Exploring the Determinants of Mentorship in Nursing among Senior Nurses in Northern Ghana. - Assibi, Z.F. (University of Ghana, 2023)
Mentorship is the backbone of successful career development and pivotal in the support of newly qualified professionals with regards to the new roles, interactions and transition in practice. Mentorship is necessary in every profession and at every level whether as a new entrant of a profession or an experienced professional assuming a new role or a new setting. In nursing, there is evidence of the positive effect of mentorship on nursing practice in relation to quality improvement, self-confidence and professionalism. This study sought to explore the determinants of mentorship in nursing among senior nurses in northern Ghana. The Bronfenbrenner’s socioecological model was used as the theoretical framework for this work. This study employed an exploratory descriptive qualitative design using nurses from two hospitals in Northern Ghana. Convenient sampling was used to select participants of the study. Fourteen senior nurses from the rank of Senior Nursing Officer and above participated in the study. Data was collected by face-to-face in-depth interview of participant on the subject matter using a semi structured interview guide. Data was analysed using thematic content analysis. Overall, five theoretical themes and three emerged themes were generated. The findings of the study revealed personal factors that influence mentorship in nursing, micro system factors that influence mentorship in nursing, meso system factors that influence mentorship in nursing, the exo system factors that influence mentorship in nursing as well as the macro system factors that influence mentorship in nursing. Also, the barriers to mentorship in nursing, benefits of mentorship in nursing as well as the recommendations necessary for success in mentorship in nursing.
MPhil. Nursing
Keywords: Mentorship; career; development; Northern Ghana